Prokrastinasi Akademik di Masa Pandemi COVID-19 pada Mata Kuliah Teori Kepribadian - Meilla Dwi Nurmala; Meitami Sofiyantala; Yuyun Yuniawati; Indri Mulyadini (Journal of Education and Counseling (JECO), 2021)
The spread of COVID-19 that requires face-to-face learning is becoming online learning or distance learning.This teaching still leaves various problems in the world of education, one of which is academic procrastinationthat occurs in student groups. The purpose of this study is that the second semester students majoring inguidance and counseling, University of Sultan Ageng Tirtayasa who is in charge of the personality theorycourse experience academic procrastination, see the causes of procrastination and how students can overcomeit. The researcher used a qualitative descriptive method with non-test interview data collection techniques tothree students. The results of this study indicate that there is academic procrastination behavior carried out bythe three students with various causes, and procrastination is more often carried out on group assignments. Andstudents are still able to overcome academic procrastination in their own way.